If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1y = -5x + b Reorder the terms: 1y = b + -5x Solving 1y = b + -5x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '1'. y = b + -5x Simplifying y = b + -5x
| -2.3y=-4.5 | | 11(-8)=x | | 190=x+.07x | | (x^2-3)(3x^2+4x-1)= | | .33x-9=11 | | 5x-6y=-19 | | 1x-41=3 | | -2(v+2)=2v-4+2(3v+1) | | T-19=17 | | 72x+16=64x+40 | | -119=3(3-4x)-4x | | .20x+8=13 | | 15+8v=8v-3(v-3) | | -4(-6c+7)=35 | | 2x+35+5x+5=180 | | .25x+7=9 | | 5x+5+2x+35=90 | | 4x^3-7x^2-5x-6= | | b+1-3b=(4+6b)-7 | | -7n+10+9n=18 | | 5x+5+2x+35=180 | | 6x-3=6x+11 | | -7n+10+9n=18 | | 5x+5+2x+35=180 | | -7n+10+9n=18 | | -7n+10+9n=18 | | -173=7+4(7k-3) | | 6y+3x=32 | | 150+35x=45 | | 30=-4a+10 | | ax-6=t | | -10h(h-2)-4=36 |